Knowledge-based Entrepreneurship: The Organizational Side of Technology Commercialization - Ulrich Witt; Christian Zellner (Max Planck Institute for Research into Economic Systems, 2005)
New knowledge with commercial potential is continually created in academic institutions. How is it turned into economically valuable businesses? This paper argues that the transfer is an entrepreneurial process. To understand this, the actions and the constraints characteristic for the entrepreneurial reshaping of the division of labor must be recognized. In the case of knowledge-based entrepreneurship, specific constraints result from the peculiarities of scientific knowledge – epitomized by contrasting tacit and encoded knowledge. Scientifically trained labor is required for transferring both forms of knowledge. However, the mode of transfer differs crucially and shapes the organizational form of commercializing new scientific knowledge.
Keywords: 330; Wissenstransfer; Innovationsmanagement; Innovation